Sosialisasi Pencegahan Bullying Dengan Literasi Pada Pendidikan Di Era Kurikulum Merdeka - Vera Ironita Christiani Sihombing; Sutar Oktaviana Tampubolon; Juniar Ivana Barus (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Bullying is an intentional or unintentional act but clearly causes discomfort, humiliation, loss, crime and suffering for the victim which can lead to an unpleasant working environment where the victim does not want such treatment at all. Bullying behavior can make the victim feel afraid and pessimistic so that the victim feels insecure, especially in the school environment they become lazy to learn because there is a feeling of uncertainty and always think negatively about themselves. One example of bullying is avoiding or isolating friends at school, mocking parents' names, hitting, and pushing friends. Thus, we as the proposer want to offer a socialization activity on the impact of bullying for senior and junior students. This activity is expected to be beneficial for students and also help the role of teachers in educating their students with literacy. In this era of the independent curriculum, students are guided to be more active in learning at school and produce work. The independent curriculum is a learning method that refers to the talent and interest approach. For this reason, students are advised to be literate by being literate, students are more diligent in accessing, understanding and using something intelligently through various activities including reading, seeing, listening, writing or speaking.